2004
DOI: 10.1210/en.2004-0582
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Consequences of Hypoxia from Birth and Dexamethasone Treatment in the Neonatal Rat: Comprehensive Hepatic Lipid and Fatty Acid Profiling

Abstract: Neonatal hypoxia is a common condition resulting from pulmonary and/or cardiac dysfunction. Dexamethasone therapy is a common treatment for many causes of neonatal distress, including hypoxia. The present study examined the effects of dexamethasone treatment on both normoxic and hypoxic neonatal rats. We performed comprehensive hepatic fatty acid/lipid profiling and evaluated changes in pertinent plasma hormones and lipids and a functional hepatic correlate, i.e. hepatic lipase activity. Rats were exposed to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 59 publications
7
33
2
1
Order By: Relevance
“…Pertinent to this study was the previous finding that dexamethasone resulted in marked hyperinsulinemia without a change in plasma glucose, indicating a state of relative insulin resistance ( 12 ). We also previously demonstrated that both leptin and ghrelin were increased by dexamethasone, but that only leptin was increased by hypoxia ( 15 ).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Pertinent to this study was the previous finding that dexamethasone resulted in marked hyperinsulinemia without a change in plasma glucose, indicating a state of relative insulin resistance ( 12 ). We also previously demonstrated that both leptin and ghrelin were increased by dexamethasone, but that only leptin was increased by hypoxia ( 15 ).…”
Section: Discussionmentioning
confidence: 52%
“…We have previously used this model of hypoxia and/or dexamethasone to examine endocrine and metabolic function in neonatal rats ( 12,14,15 ). Pertinent to this study was the previous finding that dexamethasone resulted in marked hyperinsulinemia without a change in plasma glucose, indicating a state of relative insulin resistance ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outras situações em que se costuma aplicar o uso da dexametasona são os casos de gestação com risco de prematuridade, com o intuito de acelerar o desenvolvimento de determinados tecidos e órgãos do feto (Souza et al 2001, Bruder et al 2006.…”
Section: Introductionunclassified